A utopia concreta e o ainda-não-consciente na obra de Ernst Bloch - Viana, Francisco Antonio Marques (2015)
Ernst Bloch‟s thought is quite broad, and it is usually analyzed in its messianic, utopian, mystical, features; or yet, due to its possible repercussion in Latin America and its hopeful point of view. This Dissertation investigates Bloch‟s philosophy as a source for the renovation of Marxism, in two moments which are interconnected to one sole idea: the Socialist revolution, enlightened by the liberation of man from Capitalism, and the building of a better life. The first moment is to be found in concrete utopia: an equalitarian, humanistic society, without the ill-consciousness of the division of classes and the egotism of profit, having man and his integration with nature as its subject. The second moment, consequence of the first, has its nucleus in the not-yet-conscious concept and it increases in density in man after he has (been) awakened with the transformation of society. Dialectically, the road to concrete utopia is to be found in the conjugation of the cold current of Marxism - the lucidity regarding reality -, with its warm current - revolutionary enthusiasm. There is, however, a starting point for Utopian philosophy, which is the Materialist Dialectics of historical man, the incompleteness of his trajectory, and the exit from obscurity wherein he lives, in search of himself, in the luminosity of the interlacing of theory and praxis. In such process, mediated by the anticipating will, one finds the need to review the ways of philosophy and psychoanalysis. Reviewing means thinking and overcoming difficulties so as to make Socialism the political regime mass-society chooses so that, faced with the imperatives of reality, man does not give up acting and dreaming, he does not, especially, relinquish the values of equality, friendship, and happiness on Earth. With its beginning in Aristotle and in the Aristotelism of the Left, in the Gothic thought of the Middle Ages, and in the philosophy of Renaissance, Bloch‟s hope concentrates in the awakening of rebellious man and in the building upon order starting from liberty, in the convergence of the superstructure with the structure, thus making it possible for one to live true history, so that the estrangement‟ of life does not become permanent repetition. If this happens, if philosophy and psychoanalysis acquire new knowledge, including the rediscovery of fore-knowledge [of the future] in Classical Philosophy, concrete utopia and the not-yet-conscious have the chance to overcome the capitalist illusion, thus generating horizons of hope for the construction of that which man has never experienced, a society wherein he is, at once, subject and object of its construction. What distinguishes Bloch from "Orthodox Marxism" is the open philosophical system, without ideologism, far from the delusive fetish of merchandise, next to the man who transforms and awakens to a better life. He dreams awake with a philosophy of a classless society in opposition to the philosophy of a class society